2009
DOI: 10.1017/s0007114509991826
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and DHA have opposing effects on the expression levels of histones H3 and H4 in human neuronal cells

Abstract: Zn and DHA have putative neuroprotective effects and these two essential nutrients are known to interact biochemically. We aimed to identify novel protein candidates that are differentially expressed in human neuronal cell line M17 in response to Zn and DHA that would explain the molecular basis of this interaction. Two-dimensional gel electrophoresis and MS were applied to identify major protein expression changes in the protein lysates of human Ml7 neuronal cells that had been grown in the presence and absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…In order to investigate the change in the expression levels of the histones, proteomic findings were further investigated using western blot and real-time PCR analyses. Our results have revealed the differential expression of histones, particularly histone H3 and H4 in response to DHA and zinc supplementation (Suphioglu, Sadli et al 2010b). In this study, we reported for the first time that both H3 and H4 were significantly downregulated by zinc in the absence of DHA (zinc effect) and up-regulated following DHA treatment at the physiological zinc level (DHA effect), suggesting the interrelationship between zinc and DHA in neuroprotection, which is mediated by histones (Suphioglu, Sadli et al 2010b).…”
Section: Zinc and Dha Affect Neuronal Histone Levelsmentioning
confidence: 62%
See 3 more Smart Citations
“…In order to investigate the change in the expression levels of the histones, proteomic findings were further investigated using western blot and real-time PCR analyses. Our results have revealed the differential expression of histones, particularly histone H3 and H4 in response to DHA and zinc supplementation (Suphioglu, Sadli et al 2010b). In this study, we reported for the first time that both H3 and H4 were significantly downregulated by zinc in the absence of DHA (zinc effect) and up-regulated following DHA treatment at the physiological zinc level (DHA effect), suggesting the interrelationship between zinc and DHA in neuroprotection, which is mediated by histones (Suphioglu, Sadli et al 2010b).…”
Section: Zinc and Dha Affect Neuronal Histone Levelsmentioning
confidence: 62%
“…1.3.2 Possible mechanism of the effect of zinc and DHA on H3 and H4 expression We observed a significant reduction in both mRNA and protein levels of histones H3 and H4 following zinc treatment suggesting that zinc may inhibit the transcription of histones H3 and H4 in M17 human neuronal cells (Suphioglu, Sadli et al 2010b). Histones H3 and H4 possess multiple metal response elements upstream of their start codon, which indicates the possible involvement of zinc in their transcription.…”
Section: Histonesmentioning
confidence: 85%
See 2 more Smart Citations
“…159 Interestingly, docosahexaenoic acid was also shown to increase expression of H3 and H4 histones in the same cell line. 160 By contrast, palmitate induced HAT activity, and several genes that were modulated by lipotoxicity displayed altered patterns of histone modification in clonal β-cells.…”
Section: Epigenetics Of Lipid Metabolismmentioning
confidence: 96%